Interpretative Judgment in The Framework of The International Judiciary - The International Court of Justice As an example - Jabbar, Zainab; Abed, Mustafa (Journal of Legal Sciences, 2023)
That the International Court of Justice is a court of first and last instance, it is a fundamental principle that its rulings are final and cannot be appealed as stipulated in Article 60 of the Statute. Nevertheless, the provision of this Article provides that the States parties to the case may request an interpretation of the decision, When certain conditions are available, the International Court of Justice has traditionally issued interpretative rulings when the ruling is marred by any ambiguity or ambiguity. Final determination of judgment and res judicata, in the case of interpretation, if a decision or part of a decision is ambiguous, it may prove impossible for the States Parties to comply with it, and then a request for interpretation may be exactly the best way to ensure compliance and achieve res judicata as indicated The Court recently, the process of interpretation is based on the priority of the res judicata principle that must be preserved Specifically, it is the subject of the study.